Mg/Ca ratios of two Globigerinoides ruber (white) morphotypes: Implications for reconstructing past tropical/ subtropical surface water conditions - Steinke, S; Chiu, Hy; Yu, Ps; Shen, Cc; Lowemark, L; Mii, Hs; Chen, Mt (Geochemistry, Geophysics, Geosystems, 2005)
Tests of the planktonic foraminifer Globigerinoides ruber ( white; d'Orbigny) have become a standard tool for reconstructing past oceanic environments. Paleoceanographers often utilize the Mg/Ca ratios of the foraminiferal tests for reconstructing low-latitude ocean glacial-interglacial changes in sea surface temperatures (SST). We report herein a comparison of Mg/Ca measurements on sample pairs (n = 20) of two G. ruber (white) morphotypes (G. ruber sensu stricto (s. s.) and G. ruber sensu lato ( s. l.)) from surface and downcore samples of the western Pacific and Indian Oceans. G. ruber s. s. refers to specimens with spherical chambers sitting symmetrically over previous sutures with a wide, high arched aperture, whereas G. ruber s. l. refers to a more compact test with a diminutive final chamber and small aperture. The G. ruber s. s. specimens generally show significantly higher Mg/Ca ratios compared to G. ruber s. l. Our results from the Mg/Ca ratio analysis suggest that G. ruber s. l. specimens precipitated their shells in slightly colder surface waters than G. ruber s. s. specimens. This conclusion is supported by the differences in delta O-18 and delta C-13 values between the two morphotypes. Although it is still unclear if these two morphotypes represent phenotypic variants or sibling species, our findings seem to support the hypothesis of depth and/or seasonal allopatry within a single morphospecies.